Primary mucosa-associated lymphoid tissue (MALT) lymphoma of the trachea: a case of surgical resection and long term survival. Issue 1 (23rd December 2004) - Okubo, K; Miyamoto, N; Komaki, C
Abstract : Primary malignant lymphoma of the trachea is rare. The case history is presented of a 44 year old woman with a mucosa-associated lymphoid tissue (MALT) lymphoma of the trachea who was treated with a tracheal resection and reconstruction. The patient has been free from the disease for 53 months, which confirms the favourable prognosis of MALT lymphoma following local treatment.